A theoretical-methodological proposal for the use of ICTs in English classes in Brazilian educational institutions - Schaefer, Rodrigo; Heemann, Christiane (Revista Letras Raras, 2021)
A possible way to provide oral and written English practice by using Information and Communication Technologies (ICTs) is through telecollaborative activities (SCHAEFER; HEEMANN, 2019). O’Dowd (2013) defines telecollaboration as the use of online technologies in the context of language teaching and learning with students who are geographically dispersed. Another possibility to favor the practice of English using ICTs is through digital stories, understood as the inclusion of multiple digital resources in storytelling (CASTAÑEDA, 2013). Drawing on scholars such as Brammerts (1996, 2003), Lambert (2006, 2007), Almeida (2014), O’Dowd (2012, 2013), Tumolo (2015) and Schaefer (2019), this study aims at presenting a theoretical-methodological proposal, which involves the use of ICTs, for English classes in Brazilian educational institutions. On the basis of the presentation of our theoretical-methodological proposal, we suggest that activities that utilize ICTs have the potential to produce challenges that may lead to language learning, student motivation, collaborative work and reflection.